Physical activity during postpartum period - an analysis of the latest studies and guidelines - Katarzyna Chawrylak; Maria Kubas; Katarzyna Krzemińska; Julia Kuszneruk; Magdalena Kłusek (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Purpose: Guidelines recommend at least 150 minutes of moderate-intensity aerobic activity weekly for postpartum women to enhance cardiovascular fitness, muscle strength, weight management, and mental health, particularly in alleviating postpartum depression (PPD). This review aimed to overview physical activity (PA) in postpartum women and identify key aspects to improve their health and quality of life.   Methods: A literature review was conducted using PubMed and Google Scholar, focusing on articles from 2015 to 2024, including observational studies, clinical trials, meta-analyses, and systematic reviews. Non-English articles and book chapters were excluded.   State of Knowledge: Studies highlighted the effectiveness of various exercise regimens for postpartum conditions. Trunk stabilization exercises significantly reduced lumbopelvic pain and disability. Exercise training impacted maternal vascular health and blood pressure, with regular exercise reducing blood pressure, preventing long-term cardiovascular diseases. Innovative approaches, such as progressive muscle relaxation exercises (PMRE) combined with online health counseling, reduced PPD and enhanced maternal attachment. Smartphone app-based pelvic floor muscle training (PFMT) reminders increased adherence and improved short-term pelvic floor muscle (PFM) function, showing potential long-term benefits.   Summary: This review provides strong evidence for structured PA programs in postpartum care, offering benefits from pain reduction and improved cardiovascular health to enhanced mental well-being. Future research should identify barriers to PA adherence and develop tailored interventions for postpartum women.